Human resources management in the field of Justice: legal regulation - Shevchenko, Anna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
In the article is analyzes the legal regulation of human resources management in the judicial system of Ukraine.When the issue of personnel in the judiciary sounds, the primary issue is the organization of the selection of judges, which is quite logical and natural phenomenon in the conditions of improving the quality of justice. Instead, the work of the cadre is no less important as its functions ensure the effective selection of judges, the stability and professional growth of the judicial corps and other court staff.There are a narrow and broad approach to personnel functions, the boundaries of which are important to evaluate based on the staffing services. In according to the narrow approach, the latter are exclusively judges. Instead, the broad approach encompasses a staffing strategy for all staff involved in the administration of justice.Personnel management is an independent function in the system of organization of the judicial branch, covering both current hr-tasks (selection, preparation, formation, development, assessment of professional competence of dismissal), as well as a strategic goal (improving the level of legal protection by improving the quality of justice) in the field of human resources management.The nature of the current legal support for staffing is due to the following factors: judicial reform and increased public participation in the formation of a quality judicial body; increasing requirements for the disciplinary behavior of judges; raising of anti-corruption standards in the state regarding the civil servants and the patronage service.The modernization of human resources in the judicial bodies is being traced, as evidenced by the emergence of legislative norms on the extension of personnel procedures at the stage of selection of judges and the expansion of the range of subjects involved in human resources processes, enhancement of the institutional capacity of the SCA in the organizational and human resources of justice.Enhancing the participation of civil society in the formation of a high-quality judicial corpus carries the risk of mass use of decisions in formulating the opinion on the dishonesty of judges, as well as exceeding the limits of permissible public gathering of information about judges in the search for signs of integrity privacy and dignity. In this regard, there is a need to further improve the legislative and regulatory support for staffing and related processes in the judiciary.